2022
DOI: 10.1097/lgt.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Symptoms and Diagnosis of Vulvar Lichen Sclerosus in Premenopausal Women: A Cross-Sectional Study

Abstract: Objectives/PurposePresenting symptoms of vulvar lichen sclerosus (LS) specific to premenopausal women are not well reported in the literature and may differ from those in postmenopausal women. This study aimed to characterize the presentation of vulvar LS among premenopausal women.Materials and MethodsAn observational web-based study was conducted in premenopausal women with biopsy-confirmed vulvar LS between the ages of 18–50 years. Participants completed a 28-question survey evaluating characteristics of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…He et al tested 8 kinds of autoantibodies in 142 patients with lichen sclerosus and found that 48% of the patients were positive for autoantibodies (25). Krapf et al recorded the clinical manifestations and long-term follow-up of 40 cases with Vulvar lichen Sclerosus (26), their results also showed that the HLADQB10201 allele was present in 80% of patients and 41.8% of controls (RR: 3.71; P≤0.0042). Altogether, various pathological types show different therapeutic responses, and the reasons for this need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…He et al tested 8 kinds of autoantibodies in 142 patients with lichen sclerosus and found that 48% of the patients were positive for autoantibodies (25). Krapf et al recorded the clinical manifestations and long-term follow-up of 40 cases with Vulvar lichen Sclerosus (26), their results also showed that the HLADQB10201 allele was present in 80% of patients and 41.8% of controls (RR: 3.71; P≤0.0042). Altogether, various pathological types show different therapeutic responses, and the reasons for this need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, VLS can affect women of any age and the proportion in fertile women could be higher than expected. In a survey of women of reproductive age with histological confirmation of VLS, the mean age of diagnosis was 32 years, with symptom onset at 27 years ( 14 ). Furthermore, up to 40% of the surveyees described symptoms prior to menopause or they were diagnosed with asymptomatic VLS during the gynecologic examination ( 11 , 15 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Lichen sclerosus (LS) is a chronic, inflammatory skin condition affecting the anogenital epithelium in women of all ages, including premenopausal women. 1,2 The true prevalence of VLS is unknown, with estimates ranging from 1.7% in one US general gynaecology practice to 3% in an elderly Israeli population. 3,4 The prevalence of VLS in reproductiveage women is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…12 On the other hand, reproductive-age women with VLS may be affected more by sexual symptoms than by pruritus. 2,11 A study of reproductive-age women with 'early onset' LS indicates that the use of anti-androgenic oral contraceptive pills was associated with symptoms and diagnosis of VLS. 13 Hormonal changes during pregnancy include increases in both estrogen and androgen levels, which may influence VLS symptom profile and severity during pregnancy and postpartum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation